Feasibility Analysis of Geography Textbooks for Class X Semester 2 Hydrosphere Material - Santi, Intan Prama; Angriani, Parida; Hastuti, Karunia Puji; Adyatma, Sidharta; Aristin, Nevy Farista (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
A good textbook must be by the applicable curriculum. The subject matter presented in the textbook must be by the correct concept. However, many textbooks on the market still present wrong concepts. Conceptual errors are permanent in students' thinking, making them difficult to change. Assessment of geography textbooks needs to be carried out to determine the conformity of the textbook content with the quality standards determined by the Curriculum, Standards, and Educational Assessment Agency (BSKAP). Assessment standards include content, language, presentation, and design standards. The object of research is the geography textbook published by Erlangga, the Merdeka Curriculum edition. The material analyzed is the hydrosphere material presented in class X semester 2. This research uses descriptive content analysis techniques, using a quantitative approach. The data obtained is analyzed by scoring each component item, calculating percentages, determining eligibility criteria, and describing the assessment results. Based on the overall assessment results, the percentage was 81%. The results of this assessment are included in the appropriate criteria. However, several suggestions are given by the teacher, so that the author can consider them in revising or improving the book.